30-day mortality among very old patients admitted to European intensive care units for major trauma - Duncan, Chris F; Lonsdale, Dagan O; Farrah, Helen; Farnell-Ward, Sarah; Ryan, Christine; Watson, Ximena; Cecconi, Maurizio; Fjølner, Jesper; Szczeklik, Wojciech; Moreno, Rui; Artigas, Antonio; Joannidis, Michael; et al. (S. Karger AG, 2024)
Introduction: Cases of major trauma in the very old (over 80 years) are increasingly common in the intensive care unit (ICU). Predicting outcome is challenging in this group of patients as chronological age is a poor marker of health and poor predictor of outcome. Increasingly, decisions are guided by the use of organ dysfunction scores of both acute conditions (e.g., sequential organ failure assessment [SOFA] score) and chronic health issues (e.g., clinical frailty scale [CFS]). Recent work suggests that increased CFS is associated with a worse outcome in elderly major trauma patients. We aimed to test whether this association held true in the very old (over 80) or whether SOFA had a stronger association with 30-day outcome. Methods: Data from the very elderly intensive care patient (VIP)-1 and VIP-2 studies for patients over 80 years old with major trauma admissions were merged. These participants were recruited from 20 countries across Europe. Baseline characteristics, level of care provided, and outcome (ICU and 30-day mortality) were summarised. Uniand multivariable regression analyses were undertaken to determine associations between CFS and SOFA score in the first 24 h, type of major trauma, and outcomes. Results: Of the 8,062 acute patients recruited to the two VIP studies, 498 patients were admitted to intensive care because of major trauma. Median age was 84 years, median SOFA score was 6 (IQR 3, 9), and median CFS was 3 (IQR 2, 5). Survival for 30 days was 54%. Median and interquartile range of CFS were the same for survivors and non-survivors. In the logistic regression analysis, CFS was not associated with increased mortality. SOFA score (p < 0.001) and trauma with head injury (p < 0.01) were associated with increased mortality. Conclusions: Major trauma admissions in the very old are not uncommon, and 30-day mortality is high. We found that CFS was not a helpful predictor of mortality. SOFA and trauma with head injury were associated with worse outcomes in this patient group.
Keywords: Elderly; Frailty; Intensive care; Mortality; Trauma; Taverne; Geriatrics and Gerontology; Ageing; Journal Article